ذہنی صحت کا جامع تصور: قرآن و سنت کی روشنی میں تحقیقی جائزہ: A Comprehensive Concept of Mental Health in the Light of the Qur’an and Sunnah: An Analytical Study - Dr. Asma Aziz; Sidra Yaseen (jihat-ul-islam, 2025)
Mental health is an essential component of overall human well-being, affecting emotional stability, behavioral balance, and spiritual harmony. While modern psychology provides numerous frameworks for understanding mental well-being, Islamic teachings rooted in the Qur’an and Sunnah offer a comprehensive and spiritually enriched perspective on mental health. This research aims to explore the holistic Islamic concept of mental health, highlighting its theological, moral, emotional, and behavioral dimensions. The Qur’an places great emphasis on inner peace (ṭuma’nīnah), trust in Allah (tawakkul), gratitude (shukr), patience (ṣabr), and remembrance of Allah (dhikr) as foundational elements of mental and emotional stability. The Sunnah of the Prophet Muḥammad (PBUH) offers practical guidance through supplications, ethical behavior, social relationships, and positive coping strategies for stress, anxiety, and grief. This paper examines how these teachings collectively contribute to a mentally resilient and spiritually grounded personality. Furthermore, the study analyzes causes of psychological distress from an Islamic perspective, such as spiritual emptiness, sin, lack of purpose, and disconnection from divine guidance. It also evaluates preventive and therapeutic strategies embedded in Islamic tradition that promote mental well-being, such as regular prayers, social solidarity, sincere repentance, and reliance on divine mercy. In conclusion, the research affirms that Islam provides a timeless, comprehensive framework for mental health that addresses not only psychological symptoms but also spiritual and moral dimensions, thereby offering an integrated model for individual and communal well-being.